Preparation of LiNiVO4 nano-powder using tartaric acid as a complexing agent - Titipun Thongtem (2018)
LiNiVO4was prepared from Li2CO3, Ni(CH3COO)2·4H2O and NH4VO3using tartaric acid as a complexing agent with 1:1-1:4 mole ratios of metals:tartaric acid and subsequent calcination at 350-700 °C for 6-12 h. Inverse spinel LiNiVO4was detected using XRD. FTIR and Raman analyses revealed the presence of stretching band of VO4tetrahedrons. Only Ni, V and O were detected by EDX. The 1:4 mole ratio for the product with 450 °C calcination for 6 h analyzed by SEM, TEM and electron diffraction (ED) composes of LiNiVO4nano-powder with 10-30 nm in diameter. © 2006 Elsevier Ltd and Techna Group S.r.l.